'Latent reserves': A hidden treasure in National Forest Inventories. (5th October 2020) - Portier, Jeanne; Wunder, Jan; Stadelmann, Golo; Zell, Jürgen; Abegg, Meinrad; Thürig, Esther; Rohner, Brigitte
Abstract: In a Europe shaped by centuries of forest management, the task of today's scientists in characterising, understanding and modelling natural forests is highly challenging. Although numerous forest reserves exist, most remain hardly comparable case studies. Contrarily, National Forest Inventories (NFIs) consist of systematically distributed sample plots with varying time since last intervention and provide representative data. These characteristics make NFIs a unique opportunity to investigate hidden natural forests. Here we propose using NFI plots free of human influence for >40 to >70 years ('latent reserves') to conduct large‐scale studies on near‐natural forests. We tested this original concept in Swiss forests. We characterised compositional and structural attributes of 'latent reserves' and compared them with those of managed forests to assess whether the former demonstrated more signs of naturalness than the latter. As an example of an application, we analysed the tree‐ and stand‐level factors affecting natural tree mortality in 'latent reserves'. Up to 15.3% of Swiss NFI plots fulfilled the criteria of 'latent reserves', and most of these plots were distributed at mid‐ to high elevations where accessibility and management opportunities are limited. 'Latent reserves' showed more signs of naturalness than managed forests—a higher proportion of broadleaves, higher mortality rates, higher stand density and more deadwood. However, their size structure and basal area did not differ from those of managed forests, most likely because of a lower site productivity. Although 'latent reserves' were transitioning towards a natural state, more time without management might be required for these forests to become fully detached from the effects of past management, especially at high elevations. Mortality analyses in 'latent reserves' showed that species‐specific tree mortality had a U‐shaped response to tree size, was negatively related to tree growth and was higher when competition was stronger. Synthesis . Our findings demonstrate the potential of 'latent reserves' to study near‐natural forests at the country level, and point to further opportunities for larger‐scale collaborations. Investigating 'latent reserves' represents a first step towards a deeper understanding of such forests using existing long‐term data and shows promise for further research in Europe. Abstract : Europe faces a strong lack of data on natural forests due to centuries of forest management activities. National Forest Inventories conceal an important fraction of sample plots that have been free of human intervention for decades. These 'latent reserves' show great potential to improve our understanding of near‐natural forests at the European scale. Image shows spruce‐dominated forest sample plots from the Swiss National Forest Inventory. (L) 'Latent reserve' ‐ no human intervention for at least 40 to 70 years. (R) Managed forest ‐ human intervention occurred in the last 40 years. Résumé: Dans une Europe façonnée par des siècles d'aménagement forestier, les scientifiques font aujourd'hui face à la difficile tâche de caractériser, comprendre et modéliser les forêts naturelles. Bien qu'il existe de nombreuses réserves forestières, la plupart d'entre elles correspondent à des cas d'étude isolés et guère comparables. A l'inverse, les Inventaires Forestiers Nationaux (IFN) sont constitués de placettes d'échantillonnage systématiquement distribuées ayant été soumises à des activités forestières à différentes périodes, fournissant ainsi des données représentatives. Ces caractéristiques font des IFN une opportunité unique d'étudier les forêts naturelles dont l'existence est encore insoupçonnée. Nous proposons d'utiliser les placettes d'échantillonnage des IFN n'ayant subi aucune intervention humaine depuis >40 à >70 ans (les 'réserves latentes') afin de conduire des études à large échelle sur les forêts quasi‐naturelles. Nous avons testé ce concept original dans les forêts suisses. Nous avons caractérisé les attributs compositionnels et structurels des 'réserves latentes' et les avons comparés à ceux des forêts aménagées afin d'évaluer si les premières montraient davantage de signes de naturalité que les secondes. A titre d'exemple d'application, nous avons analysé les facteurs à l'échelle de l'arbre et du peuplement affectant la mortalité naturelle des arbres dans les 'réserves latentes'. Nous proposons d'utiliser les placettes d'échantillonnage des IFN n'ayant subi aucune intervention humaine depuis >40 à >70 ans (les 'réserves latentes') afin de conduire des études à large échelle sur les forêts quasi‐naturelles. Nous avons testé ce concept original dans les forêts suisses. Nous avons caractérisé les attributs compositionnels et structurels des 'réserves latentes' et les avons comparés à ceux des forêts aménagées afin d'évaluer si les premières montraient davantage de signes de naturalité que les secondes. A titre d'exemple d'application, nous avons analysé les facteurs à l'échelle de l'arbre et du peuplement affectant la mortalité naturelle des arbres dans les 'réserves latentes'. Synthèse . Nos résultats démontrent le potentiel des 'réserves latentes' dans l'étude des forêts quasi‐naturelles à l'échelle nationale, et pointent vers des opportunités de collaborations à plus larges échelles. Etudier les 'réserves latentes' représente une première étape vers une meilleure compréhension de ces forêts en utilisant des données à long terme déjà existantes et constitue une avenue prometteuse pour de futures recherches en Europe.